Retooling phage display with electrohydrodynamic nanomixing and nanopore sequencing. Issue 24 (12th November 2019) - Raftery, Lyndon J.; Howard, Christopher B.; Grewal, Yadveer S.; Vaidyanathan, Ramanathan; Jones, Martina L.; Anderson, Will; Korbie, Darren; Duarte, Tania; Cao, Minh Duc; Nguyen, Son Hoang; Coin, Lachlan J. M.; Mahler, Stephen M.; et al.
Abstract : High throughput screening of phage display libraries for target binding molecules using electrohydrodynamic nanomixing and nanopore sequencing. Abstract : Phage display methodologies offer a versatile platform for the isolation of single-chain Fv (scFv) molecules which may be rebuilt into monoclonal antibodies. Herein, we report on a complete workflow termed PhageXpress, for rapid selection of single-chain Fv sequences by leveraging electrohydrodynamic-manipulation of a solution containing phage library particles to enhance target binding whilst minimizing non-specific interactions. Our PhageXpress technique is combined with Oxford Nanopore Technologies' MinION sequencer and custom bioinformatics to achieve high-throughput screening of phage libraries. We performed 4 rounds of biopanning against Dengue virus (DENV) non-structural protein 1 (NS1) using traditional methods (4 week turnaround), which resulted in the isolation of 19 unique scFv clones. We validated the feasibility and efficiency of the PhageXpress method utilizing the same phage library and antigen target. Notably, we successfully mapped 14 of the 19 anti-NS1 scFv sequences (∼74%) with our new method, despite using ∼30-fold less particles during screening and conducting only a single round of biopanning. We believe this approach supersedes traditional methods for the discovery of bio-recognition molecules such as antibodies by speeding up the process for the development of therapeutic and diagnostic biologics.